Black Garlic: Processing, Composition Change, and Bioactivity. Issue 3 (20th June 2020) - Jing, Hao
Abstract : Garlic ( Allium sativum L.) has been not only consumed as flavor vegetable, but also recorded as a prophylactic and therapeutic medicinal plant since ancient time. Its characteristic pungent flavor limited its application in food product development. Black garlic made from garlic by a thermal processing under certain temperature and relative humidity tastes slightly sweet without pungent flavor, and has extended shelf‐life. The present work presented recent development in black garlic processing scheme, composition changes during thermal processing of black garlic, especially formation of Maillard reaction products, and some bioactive properties of black garlic. GRAPHICAL ABSTRACT: